A Sliding Lamp for Room Lighting - Rompis, Lianly; Dame, Kristian; Rottie, Ronaldo; Pandelaki, Steven; Polly, Victori (European Journal of Applied Sciences, 2022)
Room lighting is very important because good lighting will nourish our eyes and minds when reading so that what is read can be applied correctly. Reading activities will not feel tiring, but rather fun for everyone, especially families and children. Reading is one of the main activities of humans that will continue needed for generations. Poor lighting will hamper the human ability to understand and recognize the development of science and technology in order to improve living standards and economic prosperity. So far, the lighting produced by humans with the creation of electricity and lamps has been very useful in helping human works, especially in helping to create good lighting for the needs of the learning process. Technological developments and the current era of the Industrial Revolution 4.0 require energy efficiency and proper treatment in helping the order of human life. There have been many technologies, methods and procedures created to support the advancement of electricity and the development of alternative energy. This paper describes the basic concept of designing a sliding lamp prototype for room lighting which is expected to contribute to science and technology and can offer good solution for creating better lighting according to the needs of society, institutions, and industry. The basic concept of our research will be further developed into a further concept by the Research Lecturers Team of the Faculty of Engineering, Unika De La Salle Manado. The research methodology is literature study, diagrams and drawings design, circuit design and simulation. The results provide something positive for future works that can be further developed and perfected.